ALASAN TALCOTT PARSONS TENTANG PENTINGNYA PENDIDIKAN KULTUR - Syawaludin, Mohammad (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2014)
This research has a title the Inclusive Culture Education: aStudy about the Parsonian Concept of system and cultureharmony. This research focuses on the inclusive culture ofthe education boarding and the relation of the Islamicinstitutions example Pesantren or the sub concept likekhalaqah, taddabur, taddarus, al-kulliyah. Through the analysisof period, this research can describe the progress from thefirst process of the structure development and theexpansion of the inclusive culture education in Islamiceducation traditions for Indonesia case. Like khalaqah isaction by youth movement Islamic can change fromexclusive oriented to inclusive committed. The method ofthis study uses qualitative approach of case studies. Thisapproach intends to rationalism, social reality, politic, andculture. Besides, the choosing of single case study methodis research strategy that helps the researcher to investigate aprogram, phenomenon, activity, process, and individualgroup accurately.